(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2018)
Generally, Plants have immense potential in the wounds management and treatment.In Chinese herbology, Hibiscus plant is a potent herb and have a good medicinal values but not scientifically approached. The present study aims to investigate the wound healing and antimicrobial activity of ethanolic extract of Hibiscus hirtus Linn.(HH). Wound healing activity was carried out by excision, incision and burn wound models. Antimicrobial activity was determined by cup plate method. Healing rate was assessed from the rate of wound contraction, epithelialization rate, tensile strength, hexosamine and hydroxyproline content. From the obtained results, it was indicated that the wound contraction and increased tensile strength of Hibiscus hirtus extract exhibits potent wound healing capacity. Hexosamine and hydroxyproline expression were also correlative with the pattern of healing observed. Histological observation indicates that the wounds treated with Hibiscus hirtus extract and povidone iodine have reduced scar formation and enhances fibroblast proliferation, angiogenesis, keratinization and epithelialization. The Hibiscus hirtus extract has excellent antimicrobial activity against the various organisms. Wound healing activity of our ethanolic extract of Hibiscus hirtus has shown the good effect which has proved by different physical, histological, biochemical parameters. Significant antimicrobial activity shown may be due to major active constituents present in plant.